A Minireview on Statin Therapy - Ebner, Erich (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Clinical experience, as well as chemical analyses, case observations, and statistics, reveal that statin medication causes significant harm. The necessity of cholesterol metabolism for brain functionality will be the focus. Because the blood-brain barrier doesn't really allow circulating blood to permeate, cells have a sensitive balance of cholesterol metabolism and must govern their needs independently, the importance and consequences of Statin therapy must be reconsidered.